PENGARUH CORPORATE SOCIAL RESPOSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN SEKTOR PERTANIAN DAN PERTAMBANGAN - Windy Ayu Atwiningsih; Pujianto Pujianto (Jurnal Ekonomi, Bisnis dan Social, 2023)
The aim of this research is to examine the impact of Corporate Social Responsibility and Good Corporate Governance on the tendency to minimize tax payments in companies within the agricultural and mining sectors listed on the Indonesia Stock Exchange during the period of 2019 - 2021. This study utilized a sample of 120 companies selected through purposive sampling. Tax aggressiveness was measured using the Effective Tax Rate (ETR), Corporate Social Responsibility was assessed based on 91 disclosure criteria following the Global Reporting Initiative (GRI) fourth version or GRI-G4, while Good Corporate Governance was measured using variables such as Independent Board of Commissioners, Board of Directors, and Audit Committee. The findings indicate that Corporate Social Responsibility does not demonstrate a significant impact on the tendency to minimize tax payments. Good Corporate Governance, measured by the Board of Directors variable, has a significant influence on tax aggressiveness. On the other hand, the variables of Independent Board of Commissioners and Audit Committee do not have a significant impact on tax aggressiveness.